Evolving geometries, topologies, and apertures in fracture networks: Quantitative insights from lattice modeling - Mathur, Bakul; Prabhakaran, Rahul; Köhn, Daniel (Forces in Mechanics, 2023)
Fracture networks are crucial in controlling rock mass permeability. Some of the important features of the fracture networks like the density, interconnectivity, spatial distribution, and fracture apertures determine the success of the subsurface operations. Fracture networks can be studied with analogue studies, physical experiments, and numerical modeling. In this study, we analyse the evolution of a two-dimensional fracture network under gravitational and shear loads using the lattice modeling capabilities of the microstructural modeling environment “Elle”. The simulation cases include varying gravitational loads and Young's moduli of the formations. The topological progression of the modeled fracture network from isolated to interconnected nodes depicts a realistic network evolution process. The study shows that the rock stiffness exhibits a direct correlation with the number of fractures influencing the average aperture size of the network. A higher gravity load resulted in the development of a sparse fracture network. Stiffer rock models also showed an early onset of fracturing.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Aperture; Elle; Fracture; Lattice; Network

Investigating seismicity rates with Coulomb failure stress models caused by pore pressure and thermal stress from operating a well doublet in a generic geothermal reservoir in the Netherlands - Hutka, Gergo András; Cacace, Mauro; Hofmann, Hannes; Mathur, Bakul; Zang, Arno (Netherlands Journal of Geosciences-Geologie En Mijnbouw, 2023)
The utilisation of geothermal energy in the Netherlands is primarily focused on deep sedimentary aquifers, which are often intersected by major faults. Geothermal operations (i.e. fluid production and injection) may alter the effective stress state along these faults and trigger induced seismic events. Pore pressure perturbations have been generally considered the main driver of injection-induced seismicity. However, thermal stresses caused by temperature gradients between the re-injected cold fluid and the reservoir rock may also contribute to the triggering of earthquakes in geothermal reservoirs. While existing geothermal power plants operating in sandstone reservoirs did not produce any major induced seismicity, it is a matter of debate whether a reduction in the temperature of the re-injected fluid could increase the seismic hazard potential. In this study, we applied modified Gutenberg-Richter statistics based on frictional Coulomb stress variations implemented in a coupled thermo-hydro-mechanical model to estimate the seismic hazard caused by the operation of a geothermal doublet. We conducted a systematic parametric study to assess and rank the impact of different intrinsic (geological) and extrinsic (operational) parameters on the induced seismic hazard potential. We identified a competing mechanism between induced variations in pore pressure and thermal stress within the reservoir in controlling induced seismicity. We found that stress changes induced by pore pressure variations are the main cause of seismic hazard, although thermally induced stresses also contribute significantly. The results indicate that by optimising the operational parameters it is possible to increase production efficiency while maintaining a long-term control over the fluid injection-induced seismicity.
CRIS-Team Scopus Importer:2023-07-21
Keywords: deep geothermal energy; Gutenberg-Richter statistics; hazard assessment; induced seismicity; Mohr-Coulomb failure approach; thermal stresses

Thermo-hydro-mechanical simulation of cooling-induced fault reactivation in Dutch geothermal reservoirs - Mathur, Bakul; Hofmann, Hannes; Cacace, Mauro; Hutka, Gergo András; Zang, Arno (Netherlands Journal of Geosciences-Geologie En Mijnbouw, 2024)
Geothermal energy is one of the most viable sources of renewable heat. However, the potential risk of induced seismicity associated with geothermal operations may slow down the growth of the geothermal sector. Previous research has led to significant progress in understanding fluid-injection-induced seismicity in geothermal reservoirs. However, an in-depth assessment of thermal effects on the seismic risk was generally considered to be of secondary importance. This study aims to investigate the relative influence of temperature and key geological and operational parameters on the slip tendency of pre-existing faults. This is done through coupled thermo-hydro-mechanical simulations of the injection and production processes in synthetic geothermal reservoir models of the most utilized and potentially exploitable Dutch geothermal reservoir formations: Slochteren sandstone, Delft sandstone and Dinantian limestone. In our study, changes in the slip tendency of a fault can largely be attributed to thermo-elastic effects, which confirms the findings of recent studies linking thermal stresses to induced seismicity. While the direct pore pressure effect on slip tendency tends to dominate over the early phase of the operations, once pore pressure equilibrium is established in a doublet system, it is the additional stress change associated with the growing cold-water front around the injection well that has the greatest influence. Therefore, the most significant increase in the slip tendency was observed when this low-temperature front reached the fault zone. The distance between an injection well and a pre-existing fault thus plays a pivotal role in determining the mechanical stability of a fault. A careful selection of a suitable target formation together with an appropriate planning of the operational parameters is also crucial to mitigate the risk of induced seismicity. Besides the well-known relevance of the in situ stress field and local fault geometry, rock-mechanical properties and operation conditions exert a major influence on induced stress changes and therefore on the fault (re)activation potential during geothermal operations.
CRIS-Team Scopus Importer:2024-03-01
Keywords: Geothermal energy; induced seismicity; numerical modelling; slip tendency analysis; The Netherlands